Legal Relationship in The Subsidized Fertilizer Purchase and Sale Contract between CV Prima Tani and Toko Iffah - Widya Cahya Nabila; Suarlan Datupalinge; Muhammad Ikbal (Rechtsvinding, 2026)
This study aims to examine the nature of the legal relationship between CV Prima Tani and Toko Iffah regarding the sales contract for subsidized fertilizer. A normative legal research method was employed. The findings indicate that the legal relationship between CV Prima Tani acting as the seller or distributor and Toko Iffah acting as the buyer or authorized retailer of subsidized fertilizer is grounded in a sales contract that establishes rights and obligations for both parties. CV Prima Tani is obligated to supply and deliver subsidized fertilizer in accordance with established stipulations regarding quantity, type, quality, and distribution mechanisms, while Toko Iffah is obligated to make payments and distribute the fertilizer to farmers in compliance with applicable regulations. However, implementation challenges persist, such as distribution delays, limited fertilizer availability, and varying levels of understanding among the parties regarding administrative requirements and regulations governing subsidized fertilizer. The study concludes that the sales contract between CV Prima Tani and Toko Iffah has established a binding legal relationship based on the principles of freedom of contract and good faith, as well as statutory provisions. Consequently, there is a need for improved adherence to distribution procedures and more effective oversight to ensure the contract is executed in an orderly manner and yields benefits for the farming community.